Brain Metastases from NSCLC: Radiation Therapy in the Era of Targeted Therapies. Issue 10 (October 2016) - Khalifa, Jonathan; Amini, Arya; Popat, Sanjay; Gaspar, Laurie E.; Faivre‐Finn, Corinne
ABSTRACT : N/A: Brain metastases (BMs) will develop in a large proportion of patients with NSCLC throughout the course of their disease. Among patients with NSCLC with oncogenic drivers, mainly EGFR activating mutations and anaplastic lymphoma receptor tyrosine kinase gene ( ALK ) rearrangements, the presence of BM is a common secondary localization of disease both at the time of diagnosis and at relapse. Because of the limited penetration of a wide range of drugs across the blood‐brain barrier, radiotherapy is considered the cornerstone of treatment of BMs. However, evidence of dramatic intracranial response rates has been reported in recent years with targeted therapies such as tyrosine kinase inhibitors and has been supported by new insights into pharmacokinetics to increase rates of tyrosine kinase inhibitors' penetration of the cerebrospinal fluid (CSF). In this context, the combination of brain radiotherapy and targeted therapies seems relevant, and there is a strong radiobiological rationale to harness the radiosentizing effect of the drugs. Nevertheless, to date, there is a paucity of high‐level clinical evidence supporting the combination of brain radiotherapy and targeted therapies in patients with NSCLC and BMs, and there are often methodological biases in reported studies, such as the lack of stratification by mutation status. Moreover, among asymptomatic patients not suitable for ablative treatment, this strategy is challenged by the promising results associated with the administration of targeted therapies alone. Herein, we review the biological rationale to combine targeted therapies and brain radiotherapy for patients with NSCLC and BMs, report the clinical data available to date, and discuss future directions to improve outcome in this group of patients.